2018
DOI: 10.22502/jlmc.v6i1.182
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Height from Foot Dimensions

Abstract: Introduction: Height determination by measuring various body parts is of value in medicolegal investigations as well as in anthropology. The current study was conducted to analyze interrelation between foot dimensions and stature, and to predict stature from foot dimensions. Methods: The study was done in medical students where stature, foot length, and foot breadth were quantified using standard instruments. We calculated correlations between variables with correlation test and predicted stature from fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…In one study conducted in Nepal showed mean foot length in male was 23.56 cm and mean foot length in female was 21.78. (13) The result is similar to our study. In this correlation coefficient for right hand length and right foot, left hand length with left foot length and left hand length with left hand breadth were 0.262, 0.300 and 0.…”
Section: Discussionsupporting
confidence: 91%
“…In one study conducted in Nepal showed mean foot length in male was 23.56 cm and mean foot length in female was 21.78. (13) The result is similar to our study. In this correlation coefficient for right hand length and right foot, left hand length with left foot length and left hand length with left hand breadth were 0.262, 0.300 and 0.…”
Section: Discussionsupporting
confidence: 91%
“…[8] Considerable anthropometric works have been carried out to assess the stature from hand dimension, foot dimension, nasal length and craniometric analysis in Nepalese population. [9][10][11][12] This study mainly focuses to find out sexual dimorphism from hand index, to obtain cut off points for male and female and to check percentage accuracy of sex determination from hand index of Nepalese population.…”
Section: Hand Index -A Forensic Tool For Sexual Dimorphism Introductionmentioning
confidence: 99%
“…The present study takes this into the consideration and used similar measurements from the living people in north-west population of India. Various studies conducted on measurement of stature from lower limb parameters, took measurements from the left side of body according to the procedure described by the International Biological Program [1,[7][8][9][10][11][12]. It is not uncommon that a right side body part may be presented for forensic examination for its subsequent identification and stature estimation.…”
Section: Discussionmentioning
confidence: 99%